Do financing conditions pose a threat to the performance and transformation of SMEs? - Annalisa Ferrando; Rozália Pál (European Investment Bank (EIB), 2024)
The availability of internal and external financing sources significantly influences firms' investments and growth. Even profitable firms with ample financing in normal times can be adversely affected by demand and supply shocks such as the COVID-19 pandemic, the energy crisis, or the recent tightening of financing conditions. This paper examines the impact of funding difficulties on firms' investment, performance and growth during normal period and periods of external shocks, using a regression adjustment treatment effect approach. We distinguish between structural barriers to external financing and cyclical deteriorations in financing conditions, while controlling for other major investment barriers. The analysis uses survey data collected from the 1 st to 8 th vintage of the European Investment Survey (EIBIS). Empirical evidence shows that micro and small firms, as well as leading innovators, are particularly vulnerable to deteriorating funding conditions. Results indicate that firms lagging in digitalisation and green investments face more of a structural rather than a cyclical financing issue. Consequently, policy support should be oriented towards these structural financing impediments to ensure a fair and faster transformation.
Keywords: C83; D22; G32; 330; SMEs; investment gap; external funding; internal funding; financing constraints; uncertainty; investment barriers; firm performance; growth; digital and green transition